The Effect of Premature Births on Language Delay in Children: A Meta-Analysis - Sutanto, Alfiani Vivi; Tamtomo, Didik Gunawan; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: Child development problems are problems that need attention. A child can experience developmental delays in one or more developmental domains. It usually occurs in infants who born prematurely. In Indonesia, data from the Ministry of Health states that there are 675,700 premature infants in Indo